Immunomodulatory Activities of Dendrophthoe falcata (L.f) Ettingsh in Experimental Animals: In vitro and In vivo Investigations - Pattanayak, S. P.; Mazumder, P. M. (Journal of Scientific Research, 2011)
In the present study, an attempt was made to screen immunomodulatory activity of the hydroalcoholic extract (HEDF) of Dendrophthoe falcata (L.f.) Ettingsh (Loranthaceae), an Indian Ayurvedic plant, on different arms of the immune system. HEDF was evaluated for immunological function by studying delayed type hypersensitivity (DTH) to sheep RBCs, nitric oxide (NO) release from murine peritoneal macrophages, phagocytic activity of polymorphonuclear (PMN) cells in vitro and reticuloendothelial system in vivo, plaque forming cell response of splenic lymphocytes to sheep erythrocytes, haemagglutination antibody titer and neutrophil adhesion test. Significant increase in NO production by mouse peritoneal macrophages was detected in culture supernatants indicated increased phagocytic activity of macrophages. After post oral administration of HEDF in three doses of 250, 475 and 950 mg/kg body weight, a significant increase in phagocytic activity of PMN cells/reticuloendothelial system, stimulation of neutrophil function and splenic antibody secreting cells, were also noticed. Stimulation of humoral immune response was further observed with elevation in haemagglutination antibody titer. Heightened DTH reaction suggested convincing evidence for activation of cellular immune system. Present study thus confirms the immunomodulatory activity of the hydroalcoholic extract of D. falcata and the immunomodulatory responses were found to be dose dependent manner. Keywords: Dendrophthoe falcata; Antibody titer; Neutrophil adhesion; Phagocytic activity. © 2011 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi:10.3329/jsr.v3i3.7655 J. Sci. Res. 3 (3), 629-640 (2011)